Assessing the Quality and Effectiveness of Alcohol Based Hand Sanitizers Commercially Available in Mbarara City - Mugenyi, Nathan; Ninsiima, Prize; Nalunkuma, Racheal (Natural Products Chemistry & Research, 2023)
Alcohol based hand sanitizers are currently recommended for routine use in curbing the spread of the serious infectious diseases like COVID-19. This survey examined hand sanitizers marketed in Mbarara city with regards to product physical characteristics, certification, labelling and declared composition which all constitute the overall quality of the hand sanitizers. Thirty-six samples of 9 brands were randomly collected from six pharmacies and six supermarkets. These samples were assessed for certification status by verification with Uganda National Bureau of Standards (UNBS) logo and presence on the list of registered manufacturers. Parameters analyzed included physical parameters like clarity using visual inspection and pH using a pH meter; alcohol content was quantified using an alcolyzer which uses a principle of IR spectroscopy. Results revealed alcohol content ranging between 65.1% to 81.24% which were in range of UNBS; US 1693: 2017 standards. However, despite falling in the required ranges, 55.6% of brands (5) had the alcohol content within the expected 95%-105% error range, two brands had the alcohol content higher while two had them lower deviation from the label claim. Also all the 9 brands (100%) were correctly labelled and passed clarity tests. Three brands (33.3%) of the samples failed the pH test of 6-8 in the standards. There was further elucidation on the effects of these deviations and of lack of consistency. This study concluded that there is good adherence to regulatory standards by manufacturers of hand sanitizers which is important to ensure that only compliant products are available on the market.
Keywords: COVID-19; Hand sanitizers; Ethanol; IR spectroscopy; pH meter